GM-008 Implementation of an objective structutred clinical examination and evaluation checklists at an instiute of clinical pharmacy. (24th March 2015) - Zeiter, B; Bayer, M; Kraemer, I
Abstract : Background: Objective structured clinical examination (OSCE) has proved to be a reliable and valid tool for assessing the communications skills of medical students. As a consequence of introducing the practice-oriented education of pharmacy students into the clinical pharmacy curriculum, the assessment of training success also has to be re-structured. Up till now, only very few voluntary OSCEs are being performed at the pharmacy faculties in the investigated country. Purpose: To implement a reliable and valid OSCE using self-developed evaluation checklists for pharmacy students at a clinical pharmacy Institute. Material and methods: 38 students in the 6th semester of their pharmacy studies took the OSCE during the summer term of 2014. The students' success was assessed by experts (pharmacists) using self-developed evaluation checklists. The reliability of the checklists was analysed by inter-rater agreement (kappa). Post-hoc all six experts separately evaluated the performance of six students in each of the six OSCE examination units (insulin administration, inhalation, compliance, interaction, over-the-counter medicines, drug information) which was video recorded during the OSCE. Results: According to the results of the evaluation checklists 36 students (95%) passed the exam. The overall medium inter-rater agreement regarding the six units was moderate (k = 0.49). The highest inter-rater agreement was recorded for insulin administration (k = 0.83) and the lowest inter-rater agreement regarding the interaction check (k = 0.22). Conclusion: The design of the OSCE proved to be satisfactory and the evaluation checklists developed turned out to be a reliable fair tool for assessing communication skills in clinical pharmacy. References and/or acknowledgements: No conflict of interest.